1990
DOI: 10.1029/ja095ia05p06477
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron resonance precipitation of energetic electrons from the inner magnetosphere

Abstract: Cyclotron resonance between trapped energetic electrons and VLF waves produces pitch angle scattering which leads to electron precipitation in the inner magnetosphere. Previous experiments have shown that in the drift loss cone at L values from 1.5 to 1.8 the energy spectrum of the electrons above 50 keV is often dominated by a single narrow peak. The center energy of this peak varies with L in a manner characteristic of cyclotron resonance between the electrons and monochromatic VLF waves in the vicinity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…In Table 1 we summarize the likely electron precipitation energies expected from each transmitter described in this study based on the L ‐shells of the peak wave power observed in this study, the transmitter frequency, and assuming parallel (0° wave normal angle) cyclotron resonance interactions at the geomagnetic equator on each of the field lines [ Datlowe and Imhof , 1990]. We are unable to estimate the energy range for nonducted NPM waves; however, we note here that the ducted electron precipitation energy would be ∼0.5 MeV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Table 1 we summarize the likely electron precipitation energies expected from each transmitter described in this study based on the L ‐shells of the peak wave power observed in this study, the transmitter frequency, and assuming parallel (0° wave normal angle) cyclotron resonance interactions at the geomagnetic equator on each of the field lines [ Datlowe and Imhof , 1990]. We are unable to estimate the energy range for nonducted NPM waves; however, we note here that the ducted electron precipitation energy would be ∼0.5 MeV.…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to estimate the energy range for nonducted NPM waves; however, we note here that the ducted electron precipitation energy would be ∼0.5 MeV. NWC is shown to be the most effective transmitter in terms of the largest energy range of precipitation energies and is also well positioned in being west of the South Atlantic Anomaly which provides increased sensitivity of the loss of scattered electrons into the drift loss cone [ Datlowe and Imhof , 1990].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1982 the S81‐1 satellite observed a large number of occurrences (680) of VLF transmitter resonance peaks [ Datlowe and Imhof , 1990]. On the basis of the geographic distribution of events, the paper established clearly that the VLF transmitters NWC in Australia and NAA/NSS in the eastern United States are the sources of waves for nearly all of the peaks observed by that instrument.…”
Section: Introductionmentioning
confidence: 98%